Research Progress of Baicalin Interactions with the Animal Gut Microbiome - Chen, Peirong; Ma, Bingjie; Liu, Jinni; Zhang, Min; Li, Jinzhe; Wu, Haigang (Indian Journal of Pharmaceutical Education and Research, 2024)
Homeostasis of the animal gut microbiome is essential for maintaining intestinal health and normal growth and development. Baicalin is an O-glucuronidated flavonoid that possesses strong anti-bacterial, anti-inflammatory and antioxidant activities. Its addition to animal feed can alter gut microbial community composition, diversity and production of bacterial metabolites while decreasing production of pro-inflammatory cytokines and other factors that compromise the integrity of the epithelial cell barrier. This review thus summarizes the research progress of baicalin and regulation of the gut microbiota to provide guidance for the potential application of this compound for animal production as an antibiotic alternative.
Keywords: Baicalin; Gut microbiota; Mechanism; Intervention treatment; Intervention; environment; Function; Structure